IMPORTANCE OF INNOVATIONS FOR THE IMPLEMENTATION OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT IN SOCIAL ENTREPRENEURSHIP – PRACTICAL AND MANAGEMENT ASPECTS - Milkov, Todor (E-Journal VFU, 2025)
Innovations are becoming an accompanying part of every area of human development that requires progress. Innovations are a predicate for success that depends on their proper integration. A permanent social necessity is the retention and upgrading of success, predetermined by the concept of sustainable development, naturally arising as a result of global dynamic transformations. Being an invariable part of social entrepreneurship, innovations are distinguished by competitiveness. This stimulates, encourages and motivates the functioning and general development in a long-term aspect, the goal being to achieve continuous improvement. Innovations are distinguished by systematicity and continuity, which is important for social entrepreneurship, based on the tripartite model – socialization, ecology, economy. All this replicates the need to write this article.